IMPLEMENTING MONTHLY COGNITIVE MONITORING AMONG OLDER ADULTS: LESSONS FROM A ONE-YEAR PILOT STUDY. (11th November 2018) - Sadeq, N; Valdes, E; Harrison Bush, A; Andel, R
Abstract: Regular cognitive monitoring is likely to become crucial as treatments for cognitive problems become available. We used a sample of 158 older adults enrolled in a monthly cognitive monitoring study to examine participant adherence and satisfaction over one year of monitoring using the Cogstate Brief Battery—a computerized cognitive screening tool that uses playing cards to test speed, working memory, attention, and visual learning across four tasks (Identification, Detection, One Back, and One Card Learning). Information was collected on the number of days it took participants to complete their assessments after monthly reminders, and the number of subsequent reminders needed. After one year of the study, participants were asked open-ended questions about their likes, dislikes, and suggestions for study improvement. On average, participants were 74.59 years of age (SD=7.87), completed 16 years of education (SD=2.19), were mostly female (n=109), completed their monthly assessment within 3.92 days (SD=2.98) of receiving the original reminder, and required one reminder call every four months. Most participants (87%) reported feeling satisfied with their overall experience and 84% chose to continue participating indefinitely. Participants reported they liked that the study was convenient, enjoyable, and provided them with a way to challenge themselves. Participants disliked that the working memory task was disproportionately difficult compared to other tasks and that the Cogstate Brief Battery was incompatible with certain internet browsers. Based on participant suggestions, strategies for increasing satisfaction with routine cognitive monitoring include providing individualized feedback about performance and alternate platforms to complete the study (e.g., smartphone, tablet).